Pengaruh Sifat Termal Tanah Terhadap Pertumbuhan Tanaman Hortikultura Diberbagai Zona Iklim - Gea, Chelsa julian; Mendrofa, Elviana (CV. SINAR HOWUHOWU, 2024)
This study examines the influence of soil thermal properties on the growth of horticultural crops in various climate zones, namely tropical, subtropical, and temperate. Soil thermal properties parameters measured include thermal conductivity, heat capacity, and thermal diffusivity. The results showed that soils in tropical climate zones, with higher conductivity and heat capacity, support more optimal growth of horticultural crops compared to subtropical and temperate climate zones. Regression analysis showed a positive relationship between soil temperature and plant growth, where optimal soil temperature conditions enhance plant physiological activities such as germination and nutrient uptake. These results emphasize the importance of adaptive soil management strategies based on soil thermal characteristics to increase horticultural crop productivity in the face of varying climatic conditions